Brief therapy techniques in a family practice residency program - Riquelme Heras, Héctor Manuel (Gilbert Greene PhD, 2014)
Brief Therapy techniques such as clarification, relabeling, and confrontation, etc. are useful for comprehensive treatment by a family physician. This study was conducted in a hospital outpatient clinic in Mexico. The most frequent diagnoses found, and in which brief therapy techniques were applied, were poorly controlled chronic diseases, and/or patients with frequent visits, and those with behavioral disturbances. The techniques applied in a total of 228 consultations provided to 88 patients over a period of four months were clarification 32%, positive relabeling 32%, and relabeling plus clarification 21%. The mean number of consultations per patient was 2.5. Keywords: brief therapy, family medicine, holistic treatment, comprehensive treatment.